2004
DOI: 10.1007/s10067-004-0970-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life measured by the Short Form 36 (SF-36) in systemic sclerosis: correlations with indexes of disease activity and severity, disability, and depressive symptoms

Abstract: The aim of this study was to evaluate health-related quality of life (HR-QOL) in patients with systemic sclerosis (SSc), to compare it with that of patients with rheumatoid arthritis (RA), and to correlate it with other parameters. HR-QOL was evaluated by the Short Form 36 (SF-36), SSc disease activity and severity by preliminary indexes recently proposed, disability by the Health Assessment Questionnaire (HAQ), and depressive symptoms by the Beck Depression Inventory. HR-QOL perception was not statistically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 30 publications
6
67
1
3
Order By: Relevance
“…The association of depression and QoL has been described for a variety of chronic diseases [20,28,29], but is less well studied in cancer patients [30]. Charlson et al reported a correlation of BDI with most scales of the EORTC-QLQ-C30, however they included 17 patients only [31].…”
Section: Discussionmentioning
confidence: 99%
“…The association of depression and QoL has been described for a variety of chronic diseases [20,28,29], but is less well studied in cancer patients [30]. Charlson et al reported a correlation of BDI with most scales of the EORTC-QLQ-C30, however they included 17 patients only [31].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this finding is that the disease has a greater impact on physical capacity than on mental health, this being the most likely explanation, since it reflects what has been identified in other studies. (3,(24)(25)(26)(27) Another possible explanation is that the MCS subscale has less discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence estimates range between 36 percent and 65 percent for depression [2] and between 19 percent and 64 percent for anxiety [3,4], percentages which considerably exceed those of the general population. In a comparative study scleroderma patients reported even more depressive symptoms on the Beck Depression scale, than rheumatoid arthritis (RA) patients, although analysing the scores on cognitive-affective items separately, no statistical difference was found between RA and SSc patients [5]. The great variability in reported prevalence rates of depression and anxiety was attributed to methodological issues [2], because it may derive from comparisons of studies using different measurement methods, the overlap between symptoms of SSc and somatic symptoms of depression involved in certain questionnaires, and the different populations sampled (differences in age, gender, disease severity, etc.).…”
Section: Introductionmentioning
confidence: 94%
“…Studies assessing correlates of depression and anxiety have provided inconsistent results regarding gender, age, marital status, educational level, severity and subset (limited or diffuse SSc) of the disease and organ involvement. They have, however, an established relationship with pain [6,7], functional status [5,8] and fatigue [6,9], because patients with worse functional status, or experiencing higher levels of pain or fatigue, tend to report more symptoms of anxiety and depression. Moreover, depression and anxiety are associated with impaired quality of life [5,10].…”
Section: Introductionmentioning
confidence: 99%